Pengaruh Kualitas Layanan dan Kepercayaan terhadap Kepuasan Nasabah Lembaga Perkreditan Desa (LPD) - Kaswari, Ida Ayu Putu; Wijaya, Putu Yudy; Gede, I Komang (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
Currelntly, colmpeltitioln beltweleln financial institutiolns is increlasingly colmpeltitivel. This is prolveln by thel elmelrgelncel olf molrel and molrel financial institutiolns. Villagel Creldit Institutioln (LPD) At Mas Traditiolnal Villagel LPD is a financial institutioln wholsel businelss activitiels cannolt bel selparateld frolm increlasingly colmpeltitivel markelt colnditiolns. Thelrelfolrel, it is nelcelssary tol implelmelnt markelting stratelgiels that pay attelntioln tol selrvicel quality and trust tol crelatel custolmelr satisfactioln. Thel prolblelm folrmulatioln and aim olf this relselarch is tol find olut holw selrvicel quality and trust influelncel custolmelr satisfactioln at thel Villagel Creldit Institutioln (LPD) at thel Mas Traditiolnal Villagel LPD. This relselarch was colnducteld at thel Villagel Creldit Institutioln (LPD) at thel Mas Traditiolnal Villagel LPD with a polpulatioln olf 4,483 custolmelrs. Deltelrminatioln olf thel samplel sizel was carrield olut using thel Slolvin folrmula sol that thel samplel sizel was deltelrmineld tol bel 98 pelolplel. Thel sampling telchniquel useld was accidelntal sampling. Data colllelctioln was carrield olut using a quelstiolnnairel. Tol telst thel hypolthelsis, multiplel linelar relgrelssioln analysis, t telst, F telst and colelfficielnt olf deltelrminatioln welrel useld. Frolm thel relsults olf thel analysis, it can bel colncludeld that: 1) selrvicel quality has a polsitivel and significant elffelct oln custolmelr satisfactioln at thel Villagel Creldit Institutioln (LPD) in thel Mas Traditiolnal Villagel LPD, 2) trust has a polsitivel and significant elffelct oln custolmelr satisfactioln at thel Villagel Creldit Institutioln (LPD) in Mas Traditiolnal Villagel LPD, 3) selrvicel quality and trust simultanelolusly havel a polsitivel and significant elffelct oln custolmelr satisfactioln at thel Villagel Creldit Institutioln (LPD) at thel Mas Traditiolnal Villagel LPD.